2014
DOI: 10.5507/ag.2014.020
|View full text |Cite
|
Sign up to set email alerts
|

Deaf-blindness: Voices of mothers concerning leisure-time physical activity and coping with disability

Abstract: Background: Deaf-blindness (DB) is a distinct disability because of combined impairments of hearing and visual functions, causes severe difficulties in the psychosocial area, communication, social interaction, and interaction with the environment. Leisure-time physical activities (LTPA) properly planned and executed can be beneficial in providing support and facilitating coping as strategy for managing stress in families of children with disabilities. Appropriate LTPA also influence the quality of the lives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In the international literature, studies with mothers of individuals with SMD (Redmond and Richardson, 2003;Sterbova and Kdlacek, 2014;Wang and Michaels, 2010) indicated similar problems with other mothers who have children with special needs. In a study conducted to determine the support needed by mothers who have children with SMD and the problems they come across during child care (Redmond and Richardson, 2003), it was found that mothers face bureaucratic obstacles in receiving support, encountered problems with financial issues and ongoing childcare.…”
Section: K5: "O Emarlar Sonucu Geldi çOk Kötü Oldum Sanki Dünyam Bamentioning
confidence: 96%
See 1 more Smart Citation
“…In the international literature, studies with mothers of individuals with SMD (Redmond and Richardson, 2003;Sterbova and Kdlacek, 2014;Wang and Michaels, 2010) indicated similar problems with other mothers who have children with special needs. In a study conducted to determine the support needed by mothers who have children with SMD and the problems they come across during child care (Redmond and Richardson, 2003), it was found that mothers face bureaucratic obstacles in receiving support, encountered problems with financial issues and ongoing childcare.…”
Section: K5: "O Emarlar Sonucu Geldi çOk Kötü Oldum Sanki Dünyam Bamentioning
confidence: 96%
“…Literature review for Turkey indicates that parents who have children with special needs experienced similar problems, and these problems commonly were listed under the highlights such as inadequate information, child care, financial problems, future concerns, family relations, negative attitude of the environment and the need for social support (Altuğ-Özsoy, Özkahraman and Çallı, 2006;Kurt, Tekin, Koçak, Özpulat and Önal, 2008;Lafçı, Öztunç and Alparslan, 2014;Şen, 2004). Sterbova and Kdlacek (2014) examined the needs of mothers and their blind and deaf children in coping with inadequacies and the leisure activities and determined that mothers had problems regarding organizing daily life, co-participation, happiness and well-being, communication, appropriate support and service and required support in these areas. In another study examinimg the needs and support families of children with significant level of disability require (Wang and Michaels, 2010), mothers expressed that they were subject to labeling and isolation, and needed assistance in information, family and social support, finances, child care, expert support and social services regarding the disabilities and development of their children.…”
Section: K5: "O Emarlar Sonucu Geldi çOk Kötü Oldum Sanki Dünyam Bamentioning
confidence: 99%
“…There appears to be limited literature focusing on the participation of children and young people with a sensory loss (visual impairment and/or deaf) in leisure activities. Over the period 2013-2023, the researcher identified only five papers in this category (Engel-Yeger and Hamed-Daher, 2013;Perkins et al, 2013;Štěrbová and Kudláček, 2014;Ghanbari et al, 2016;De Schipper et al, 2017). A few other studies included children with a visual and/or hearing impairment but as part of a larger cohort of children with disabilities (Bedell et al, 2013;Woodmansee et al, 2016;Vänskä et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this finding was more apparent in children with a visual impairment. In a small-scale qualitative study, Štěrbová and Kudláček (2014) investigated the views of parents of children with deafblindness regarding their children's involvement in physical activities in their leisure time, perceived benefits of such activities and barriers to participation. Parents reported multiple benefits from engagement in such activities including providing a structure to the lives of their children; improving their physical health and fitness; developing wellbeing; opportunities to engage in what they described as 'normal' things; and offering support to them as parents of a child with deafblindness.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of families of children with deaf-blindness have examined sibling relationships (Heller, Gallagher, & Frederick, 1999), grandparent involvement in communication development (Shaw, 2005), and the effect of coaching on mothers’ interactions with their child with deaf-blindness (Janssen, Riksen-Walraven, van Dijk, & Ruijssensars, 2010). Štěrbová and Kudláček (2014) examined mothers’ perspectives about leisure-time physical activities for their children with deaf-blindness—needs, barriers, and beliefs—and found that access to specialized programming, adaptive equipment, and family supports facilitated participation in these activities. Dammeyer (2010) found that families’ access to a network of professionals and other parents of children with deaf-blindness influenced child outcomes.…”
mentioning
confidence: 99%